2011
DOI: 10.1055/s-0031-1275293
|View full text |Cite
|
Sign up to set email alerts
|

Update on Relapses in Unilateral Nephroblastoma Registered in 3 Consecutive SIOP/GPOH Studies - A Report from the GPOH-Nephroblastoma Study Group

Abstract: Structuring the treatment of progressive nephroblastoma as well as introducing new drugs have improved the outcome significantly. However improvement is depending on the specific risk profile. Very high risk tumours are often resistant to conventional treatment, hence an international uniform treatment concept is needed to achieve conclusive results in this small group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 24 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…Moreover, WT is considered to be caused by aberrant renal development . Although the prognosis for WT patients is good, 13% of WT patients showed a two‐year relapse after tumor diagnosis . To improve the risk assessment and therapy stratification, it is essential to identify the mechanism of WT.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, WT is considered to be caused by aberrant renal development . Although the prognosis for WT patients is good, 13% of WT patients showed a two‐year relapse after tumor diagnosis . To improve the risk assessment and therapy stratification, it is essential to identify the mechanism of WT.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the SIOP-RTSG board suggests a regimen based on unpublished but presented data from the COG 27 , including combinations of vincristine, irinotecan, cyclophosphamide, carboplatin, etoposide, and doxorubicin, followed by high-dose chemotherapy and autologous stem cell transplantation at the discretion of the treating physician. The role of upfront high-dose chemotherapy for this subgroup is under debate, but a trend towards favourable outcomes has been reported by several groups in the primary and relapsed settings [28][29][30] . Details of this suggested regimen were added as an appendix to the UMBRELLA protocol.…”
Section: Cmn Rccmentioning
confidence: 99%
“…No statistically significant evidenceinfavororagainsthigh-dosechemotherapywithautologousperipheralbloodstemcelltransplantationhasbeenreportedsofar [4].However,high-dosechemotherapyseemeda treatmentoptioneveninrelapsedpatientswithfavorablehistology at the time [9]. This patient received high-dose chemotherapytwice,however,herecurred.Metzgeretal.…”
Section: Discussionmentioning
confidence: 97%
“…Multimodality treatment including chemotherapy, surgery, and radiotherapy resulsinacurerateofapproximately90% [1].Lymphnodes metastaseswerereportedtobeindicativeofbiologicallyhigh-Ozaki/Takigawa/Ichihara/Hotta/Oze/Kurimoto/ Fushimi/Ogino/Tabata/Tanimoto/Kiura riskWilms'tumor,especiallyinolderchildren [2].AnassociationbetweenWT1mutationand11p15lossofheterozygosity (LOH) with relapse in a group of prospectively identified childrenwithverylow-riskWilms'tumorwhodidnotreceive chemotherapy was recently shown [3]. Risk factor analysis from 3 consecutive SIOP/GPOH studies showed that highriskhistology,timetorelapse,localstageIII,andcombined relapse had independent and significant impact on survival [4].AlthoughsurvivalratesafterrecurrenceofWilms'tumor have improved since the 1980s, at least 40% of patients remainwithoutcureoncurrenttreatmentregimens [1].Asignificant proportion of children with Wilms' tumor who relapsedafterinitialtreatmentwithvincristineandactinomycin could be successfully re-treated with the same regimen [5]. Patientswhorelapsedaftercombinationchemotherapycould betreatedwithsalvagetherapyincludingcyclophosphamide, etoposide, or doxorubicin [6].…”
Section: Introductionmentioning
confidence: 99%